First steps towards distinguishing Mediterranean vegetation root marks on bones: An experimental approach - Alba Macho-Callejo; Dores Marin-Monfort; Aida Gutiérrez; Sara García-Morato; Yolanda Fernández-Jalvo (PLoS ONE, 2026)
Root-bone interactions are common in buried skeletal remains, yet their diagnostic value remains largely unexplored because few controlled studies have linked root marks to specific plant types. Consequently, the potential of these marks to provide information about burial environments in archaeological, paleontological, and forensic contexts has been largely overlooked. Here, we present a long-term experimental study documenting root-induced bone modifications under natural field conditions in central Spain. Deer ribs were buried at various depths and for different lengths of time among three widespread Mediterranean trees and shrubs: holm oak ( Quercus ilex ), olive ( Olea europaea ), and grapevine ( Vitis vinifera ). Using optical and scanning electron microscopy, we identified distinct patterns of root engraving on cortical bone surfaces that varied by plant type. Holm oak roots produced sinuous, dendritic grooves; olive roots generated shallow, rectilinear markings; and grapevine roots formed linear-to-circular engravings, which were often associated with localized cracking. Mark intensity increased with burial depth and duration. These findings underscore the diagnostic value of root marks in identifying plant-specific signatures and offer a novel approach to recognizing plant activity in burial environments. This information improves taphonomic interpretations in various fields, including fossil reworking processes and forensic secondary burials.